Legal Problems to Rescind the Administrative Contract of a Government Party Under Public-Private Partnership Act, B.E. 2562 - Tuntimas, Anukool; Sutthibodee, Suksmai (Ph.D. in Social Sciences Journal, 2022)
This academic article has an objective to analyze the legal problems for the unilateral termination of the contract of the government party by applying the principles of law on public-private investment, the use of power to unilaterally terminate the contract, the United Kingdom’s Standardization of PF2 Contracts and the Public-Private Partnership Act, B.E. 2562 as the framework of study The result found that the Public-Private Partnership Act, B.E. 2562 should set the criteria and methods for the fair treatment to the private parties whom the contract were terminated for without causes by the government party as the good governance practice which the government should perform to the private contract parties.